Culture Wars and Horror Movies Social Fears and Ideology in post-2010 Horror Cinema - Gregorio-Fernández, Noelia; M. Méndez-García, Carmen (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
XI, 231 p.